2018
DOI: 10.1007/s00381-018-3929-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of Mongolian spots with an update on atypical presentations

Abstract: Physicians should be aware of atypical MS and related conditions in order to further assess these patients for risk of any underlying genetic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Diers et al [16] also reported a 2-monthold girl with Mongolian spots on the buttocks, right shoulder, both lower legs and the back of the foot. Further case reports on Mongolian spots with atypical localization have been published [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Diers et al [16] also reported a 2-monthold girl with Mongolian spots on the buttocks, right shoulder, both lower legs and the back of the foot. Further case reports on Mongolian spots with atypical localization have been published [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…All dermal melanocytoses share a common pathogenetic scenario, in which the improper migration and/or inappropriate clearance (by macrophages) of melanocytes occurs during fetal development [6]. During transdermal migration (from the neural crest to the developing epidermis), some of the melanocytes may be arrested in the dermis, thereby leading to dermal melanocytosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudo-micro-Hutchinson sign (cuticle pigmentation) may be seen Hyperpigmentation of the oral mucosa 7 Develops during the first 2 decades of life Melanocytic activation with melanin deposition in the epithelium Hyperchromic patches, localized or disseminated. In the gums, they are more common and unaesthetic, especially when there is a high smile line Mongolian spot 25 40% to 90% of black newborns. Usually disappears by the age of 7 Unknown.…”
Section: Physiological Peculiarities Of Black Skinmentioning
confidence: 99%